(3da GdbeGW Ydi JUMjM HYV eG GSJYedJg GdYGeI ef GdeYQH hGdONjd hGdehd hGdCZdGWs - (3UOjb MSf NGf GdbfhLjs
(3ChdgG (B:s
(3hHYO aEfi QCjJ cKjQkG eef QcHhG eJf dSGf GdYQH hSdchG aCdaJ gPG GdcJGH hSejJg da GdbeGW s
(3BNQgG (B:s
(3bO Je HYhf Gddg JYGdi hMSf Jhajbg JMQjQ cJGH da GdbeGW GdLGeY Hjf SeGW hCfeGW s
(3GdfSNI HgG MhGTs
(3HBNQg agQS ddeNWhWs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GddZIs